The Impact Of Social Media Marketing On Brand Awareness And Consumer Buying Behaviors - Arti Atmoj Anap (Revista Electronica de Veterinaria, 2024)
The aim of this study is to improve knowledge of the factors that precede social media marketing, how they impact purchase intention, and how local and nonlocal firms can moderate these connections. Most of the proposed direct and moderating effects are supported with the findings. Purchase intention was discovered to be determined by brand awareness, trust, community, and interaction. The correlations between brand trust and interaction with purchase intention were moderated by brand origin. By integrating the contingent influence of brand localness and non-localness, the recommended framework enhances branding research and social media marketing. The research model was empirically tested using structural equation modelling. The findings support most of the proposed direct and moderating effects. Brand trust, brand community, brand awareness and interaction were found to influence purchase intention. The report highlights the influence of social networks on brand communications and offers consumer insights that assist businesses in creating successful SMM strategies by utilising the parallels and divergences in emerging economies. Given the varying degrees of CBE and their varying effects on purchase intention, attention must be paid to the reasons behind brand participation on social media as well as the kinds of content that consumers in each nation like. Our investigation of how social media marketing affects consumer behaviour in five developing nations is what makes our study unique. We are investigating into the ways that social media marketing, brand awareness, consumer behaviour, and purchase intention relate to the country of origin in various nations.